Developing convective flow in a square channel partially filled with a high porosity metal foam and rotating in a parallel-mode. (November 2015) - Alhusseny, Ahmed; Turan, Ali; Nasser, Adel
Highlights: Increasing hollow ratio improves overall performance though it reduces heat transfer. Pore density has two dissimilar impacts on heat transfer depending on hollow ratio. Rotation improves heat transfer and overall performance but augments pressure loss. Dispersion is obvious at high porosity, low hollow ratios, low conductivity ratios. It is efficient to use metal foams in enhancing heat dissipated by rotating passages. Abstract: The development of three-dimensional heat transfer and fluid flow in a square channel rotating in a parallel-mode has been investigated numerically. The duct is partially occupied by a foam material of high porosity ε ⩾ 0.89 and subjected to a uniform wall heat flux. In regards to the influence of rotation, both the centrifugal buoyancy and Coriolis forces are considered in the current study. The generalized model is used to mathematically simulate the momentum equations employing the Boussinesq approximation for the density variation. Moreover, thermal dispersion has been taken into account with considering that fluid and solid phases are in a local thermal non-equilibrium. The governing equations are discretized according to the finite volume method with employing a hybrid differencing scheme. Computations are performed for a wide range of parameters including the hollow ratio (0 ⩽ S ⩽ 1), foam porosity (0.89 ⩽ ε ⩽ 0.97), pore density (5PPI ⩽ ω ⩽ 40PPI), solid to fluid thermal conductivity ratio (250 ⩽ κ ⩽ 4000), Reynolds number (250 ⩽ Re ⩽ 2000), and rotation number (0 ⩽ Ro ⩽ 1), while the values of characteristic temperature difference and Prandtl numbers are maintained constant at Δ Tc = 1000 °C and Pr = 0.7, respectively. Results reveal that flow resistance and heat transport are augmented with either decreasing the hollow ratio and foam porosity or increasing Reynolds and rotation numbers, while two contradictory trends are found for the impact of increasing pore density on heat transfer; either enhancing or suppressing depending on the size of hollow zone. In addition, both rotation and thermal dispersion have dominant roles in enhancing heat transfer at the higher levels of porosity or the lower values of conductivity ratios. However, these roles are reduced gradually with decreasing the foam porosity or increasing thermal conductivity ratio, but do not completely vanish. Eventually, the worth of using high porosity fibrous media in enhancing the heat transported through rotating channels has been inspected. An overall enhancement parameter is compared for the current study with a previous work regarding turbulent flow in a rotating clear channel, where it has been confirmed that the current proposal is practically justified and efficient.